Managing mucormycosis in diabetic patients: A case report with critical review of the literature. (2nd March 2021) - Beiglboeck, Fabian M.; Theofilou, Nantia E.; Fuchs, Matthias D.; Wiesli, Matthias G.; Leiggener, Christoph; Igelbrink, Sebastian; Augello, Marcello
Abstract: Background and Purpose: Rhino–orbito–cerebral mucormycosis (ROCM) is a rare and potentially fatal invasive fungal infection which usually occurs in diabetic and other immunocompromised patients. This infection is associated with high morbidity and mortality rates. Prompt diagnosis and rapid aggressive surgical debridement and antimycotic therapy are essential for the patient's survival. Herein, we reviewed the localization and treatment strategies in patients with ROCM and diabetes as an underlying condition. Furthermore, we report one case of ROCM in our department. Materials and Methods: From 117 identified studies published in PubMed, 14 publications—containing data from 54 patients—were included. All patients were diagnosed clinically and by histopathological and/or bacteriological analysis for ROCM caused by the order Mucorales. Conclusion: Uncontrolled diabetes mellitus is one of the main risk factors for ROCM. A successful management of ROCM requires an early diagnosis, a prompt systemic antifungal therapy, and a rapid aggressive surgical debridement including exploration of the pterygopalatine fossa. An orbital exenteration may be necessary.